2021
DOI: 10.1002/cad.20420
|View full text |Cite
|
Sign up to set email alerts
|

Documentation status socialization among Latinx immigrant parents

Abstract: Discriminatory legislation targeting Latinx immigrants in the United States has shifted how parents communicate with their children about the hostile political climate. One way that Latinx parents talk about and prepare their children to face prejudice is through ethnic‐racial socialization, which can promote children's positive development. Few scholars, however, have focused on how Latinx immigrant families with precarious documentation status socialize their children around issues of immigration, documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Through documentation status socialization, Latinx parents teach their children about not only the inequities experienced by members of their ethnic group but also the ways in which the family has prepared to handle these challenges (Lykes et al, 2013;Cross et al, 2021). The desire to shield children from an uncertain future is reflected in these parents' ERS, which differs from that of parents not at risk for deportation.…”
Section: Documentation Status Socializationmentioning
confidence: 99%
See 2 more Smart Citations
“…Through documentation status socialization, Latinx parents teach their children about not only the inequities experienced by members of their ethnic group but also the ways in which the family has prepared to handle these challenges (Lykes et al, 2013;Cross et al, 2021). The desire to shield children from an uncertain future is reflected in these parents' ERS, which differs from that of parents not at risk for deportation.…”
Section: Documentation Status Socializationmentioning
confidence: 99%
“…In a study conducted with Latinx immigrants living in the Midwest, documentation status socialization was reportedly part of the ERS of both documented and undocumented parents. This socialization also included parents helping their children view border crossing as necessary for survival and not always a choice (Cross et al, 2021). In addition, in a review of the ERS literature of Latinx families, Ayón et al (2020) highlighted a study in which Latinx immigrant parents reported teaching their children differences in the birthplace and documentation status of members of the same family.…”
Section: Documentation Status Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, qualitative research has documented how community‐level police violence may shape BIPOC young people’s everyday fear and worry over getting involved with the police (Smith Lee & Robinson, 2019). There is also work documenting how anti‐immigration policies create fear and anxiety for families with undocumented status (Cardoso et al., 2021), shaping the content of family communications in everyday life (Cross et al., 2021). Research that looks into these everyday experiences will help us better understand how structural‐level oppression becomes relevant in adolescents’ lives.…”
Section: Understanding and Measuring Oppression‐related Experiences I...mentioning
confidence: 99%
“…This special issue aims at narrowing gaps in the literature by bringing together contributions that extend our knowledge on the role of multiple socialization experiences. In doing so, it takes a particular focus on indicators of youth's psychological and social (mal‐)adjustment and highlights a great variety of experiences in family (Cross et al, 2021; Davis et al., 2021), school (Caravita et al., 2021; Civitillo et al. 2021; Kunyu et al., 2021; Miklikowska et al, 2021; Oczlon et al., 2021; Solomontos‐Kountouri & Strohmeier, 2021) and dynamics that arise from the interplay of both contexts (Bayram Özdemir et al., 2021; Shah et al., 2021).…”
mentioning
confidence: 99%